The lion of Mars - Holm, Jennifer L. (Random House, 2021)
Bell has spent his whole life--all eleven years of it--on Mars. But he's still just a regular kid-he loves cats, any kind of cake, and is curious about the secrets the adults in the US colony are keeping. Like, why don't have contact with anyone on the other Mars colonies? Why are they so isolated? When a virus breaks out and the grown-ups all fall ill, Bell and the other children are the only ones who can help. It's up to Bell--a regular kid in a very different world--to uncover the truth and save his family...and possibly unite an entire planet. Mars may be a world far, far away, but in the hands of Jennifer L. Holm, beloved and bestselling author of The Fourteenth Goldfish, it can't help but feel like home.